1907 N.D. Laws 179 - (:unkn) unknown (My University, 1907)
Ch. 124, § 1: Any person who with intent to commit any crime, breaks into or enters a building and commits or attempts to commit a crime by the use of nitro-glycerine, dynamite, gunpowder or any other high explosive, is guilty of a felony. Any violation of this act is punishable by imprisonment in the penitentiary of this state for not less than twenty years, and not more than forty years.
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME